AB0499 Inflammatory lung disease a potential risk factor for onset of inflammatory myopathies. (23rd January 2014) - Lundberg, I. E.; Barbasso Helmers, S.; Wikman, A. L.; Axelman, P.; Lundberg, Å.; Alfredsson, L.
Abstract : Background: Although the etiology of inflammatory myopathies is unclear, there are data indicating that myositis occurs as a result of complex interactions between genes and environmental/life style factors. Objectives: To assess the association between lung disease and the risk of developing inflammatory myopathies, myositis. Methods: In this population-based case-control study, 179 incident adult myositis cases diagnosed between 1995 and 1997 were identified from the Swedish inpatient registry. Verification of diagnosis was performed through patient records. The analysis was based on responses from a questionnaire on exposures to environmental factors from 100 cases that were alive and fulfilled the inclusion criteria and from 402 randomly selected population controls matched to cases on birth of date, gender and residency. Exposure was based upon self-reports of preceding inflammatory lung disease (pneumonia, tuberculosis or sarcoidosis). The association between inflammatory lung disease and risk of developing myositis was evaluated by calculating odds ratio (OR) together with 95% confidence interval (CI) by means of logistic regression. Results: There was an association between preceding inflammatory lung disease and diagnosis of myositis: adjusted OR 1.5, 95% CI 0.9-2.6. The median duration between the lung disease and first symptom of myositis was 30 years. Conclusions: Subjects with preceding inflammatory lung disease had an increased risk of developing myositis compared to those without such disease. Inflammatory lung disease could thus be a potential risk factor for onset of inflammatory myopathies, myositis, or a parallel phenomenon. Disclosure of Interest: None Declared